Impact of Synthesis Parameters of Multi-Walled Carbon Nanotubes on their Thermoelectric Properties - Kumanek, Bogumiła (Materials (Basel), 2019)
Carbon nanotubes have been intensively researched for many years because of a wide array of promising properties that they have. In this paper, we present the impact of synthesis parameters on thermoelectric properties of nanocarbon material. We conducted a number of syntheses of multi-walled carbon nanotubes (MWCNTs) at different temperatures (800 and 900 °C) using various amounts of catalyst (2%, 5.5%, and 9.6%) to facilitate the process. We also tested the influence of injection rate of precursor and the necessity of material purification on thermoelectric properties of MWCNTs. The electrical conductivity, thermal conductivity, and Seebeck coefficient were measurement for all samples. Based on these parameters, the values of Power Factor and Figure of Merit were calculated. The results show that the most important parameter in the context of thermoelectric properties is purity of employed MWCNTs. To obtain appropriate material for this purpose optimum synthesis temperature and appropriate content of the catalyst must be selected. The study also reveals that post-synthetic purification of nanocarbon is essential to produce an attractive material for thermoelectrics.